Strengthening Morals for Santri Through the Book of Ta'lim Muta'allim - Junedi Junedi; Arya Hasan As’ari; Mukh Nursikin (The Institute of Research and Service Community IPMAFA Pati, 2022)
Morals in modern times are felt to be fading. So many people now study only oriented to the world's pleasures without caring about how Islam will be. With the existence of the Ta'alim Muta'alim book, it is hoped that it can help overcome moral decline, wrong intentions in seeking morals, wrong in finding teachers, and how we should choose friends in studying. The method used in further research is a qualitative research method that explains how the method from the book of Ta'lim Muta'alim instills morals in students. The results of the research are: Ta'lim Muta'alim by Syekh Alzarnuji is a book of morals that is very relevant and applied to instill morals in Pesantren students. Students are not only competent in theory but are required to have good morals and attitudes and be able to distinguish between good and evil. The intention is the first thing to pay attention to because seeking the pleasure of Allah and eliminating ignorance will result in studying knowledge.